Electronic Government Services for Women (EGSW) - Noori, Atyaf Sami (2010)
This project is considered as an idea to give the women a plan to leave home or the abuse place in the convenient moment. It provides the abused women with quickly escape button from the current page to prevent increasing her abuse. Also, it allows women to reveal the problems which they are exposed freely. It exposes the problems of abused women on the web page with the advice provided to them if there was a piece of advice. In addition, it allows other women who face the same problem to see the appropriate solution or advice provided to those who live the same circumstances. This project also provides the women with the places of housing provided by the Government of abused women to turn to her after leaving their homes. Furthermore, it provides the women with all sources of books written in a woman's right to defend themselves and providing them with their last laws that have been enacted in any field.